Answer:
54
Step-by-step explanation:
3.1 2 6 divided by 2 2 = 2 (6 - 2) = 2 4. Dividing exponents : 3.2 5 6 divided by 5 2 = 5 (6 - 2) = 5 4
Answer:
2x - 2
Step-by-step explanation:
There are two steps to take here. First add together the -3 + 2 in the brackets:
2(x - 3 + 2)
= 2(x - 1)
Now use the distributive property and multiply each term in the brackets by two:
2(x - 1)
= 2x - 2
And you now have it in simplest form.
Hey!
In order to simplify this equation, we'll first have to multiply both sides of the equation by v. This will give us v on its own.
<em>Original Equation :</em>
![\frac{-3}{v} = -6](https://tex.z-dn.net/?f=%20%5Cfrac%7B-3%7D%7Bv%7D%20%3D%20-6)
<em>New Equation {Added Multiply Both Sides by V} :</em>
![\frac{-3}{v} v=-6v](https://tex.z-dn.net/?f=%20%5Cfrac%7B-3%7D%7Bv%7D%20v%3D-6v)
<em>Solution {New Equation Solved} :</em>
![-3 = -6v](https://tex.z-dn.net/?f=-3%20%3D%20-6v)
Now we'll switch sides to get v on the left side of the equation which is generally where we always want the variables to be located in these types of equations.
<em>Old Equation :</em>
![-3 = -6v](https://tex.z-dn.net/?f=-3%20%3D%20-6v)
<em>New Equation {Switched} :</em>
![-6v=-3](https://tex.z-dn.net/?f=-6v%3D-3)
Now we'll divide both sides by v to get v on its own.
<em>Old Equation :</em>
![-6v = -3](https://tex.z-dn.net/?f=-6v%20%3D%20-3)
<em>New Equation {Added Divide Both Sides by V} :</em>
![\frac{-6v}{v} = \frac{-3}{v}](https://tex.z-dn.net/?f=%20%5Cfrac%7B-6v%7D%7Bv%7D%20%3D%20%5Cfrac%7B-3%7D%7Bv%7D%20)
<em>Solution {New Equation Solved} :</em>
![v = \frac{1}{2}](https://tex.z-dn.net/?f=v%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20)
<em>So, this means that in the equation
![\frac{-3}{v} =-6](https://tex.z-dn.net/?f=%20%5Cfrac%7B-3%7D%7Bv%7D%20%3D-6)
,</em>
![v = \frac{1}{2}](https://tex.z-dn.net/?f=v%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20)
.
Hope this helps!
- Lindsey Frazier ♥
Answer:
5 units
Since they both have the same y value, just subtract the a value's x from the b's x value
Svsgheydhhdjrjejrjjfjrjdhhdd